PERANAN BAITUL MAAL WAT TAMWIL DALAM PEMBERDAYAAN USAHA MIKRO KECIL MENENGAH (STUDI KASUS PADA BAITUL MAAL WAT TAMWIL AMANAH SYARIAH PASAMAN) - Rizky Fadhilah Harahap (Adpertens: Jurnal Ekonomi dan Manajemen, 2024)
The presence of Baitul Maal Wat Tamwil is the best, most strategic and functional approach to empowering small and medium enterprises, Baitul Maal WatTamwilgroup is more agile and flexible because it is more with a sidewalk or middle to lower society. Through Baitul Maal Wat Tamwil, poor communities and small traders will be released from the bondage of the usury system (interest) and divert it to the Islamic economic system with a profit sharing system. Departing from these problems, this study aims to determine how the role of Baitul Maal Wat Amanah Ummah Tamwil in conducting micro business empowerment. The research method used in this study is qualitative research with a case study method, the results obtained from this study are expected to provide a comprehensive picture and systematically the role of Baitul Maal Wat Tamwil on micro business empowerment, which was then analyzed so that conclusions could be taken in general